Medical Ethnobiology of the Highland Maya of Chiapas, Mexico : The Gastrointestinal Diseases - Berlin, Elois Ann, 1937-; Berlin, Brent (Book collections on Project MUSE., 1996)
Whereas most previous work on Maya healing has focused on ritual and symbolism, this book presents evidence that confirms the scientific foundations of traditional Maya medicine. Data drawn from analysis of the medical practices of two Mayan-speaking peoples, the Tzeltal and Tzotzil, reveal that they have developed a large number of herbal remedies based on a highly sophisticated understanding of the physiology and symptomatology of common diseases and on an in-depth knowledge of medicinal plants. Here Elois Ann Berlin and Brent Berlin, along with their many collaborators, provide detailed in.